Exploring ethnomathematics-based multicultural education as a child-friendly approach in Banyumas: focusing on multiplication and geometry - Setiyadi, Desi; Rusilowati, Ani; Trimurtini (Jurnal Pengembangan Pembelajaran Matematika (JPPM), 2025)
The ethnomathematics approach in primary education offers the potential to conceptualize mathematics learning in a contextual, reflective, and culturally based manner. However, the integration of local culture into Indonesia's mathematics curriculum remains sporadic and lacks a systematic structure. This study aims to describe the implementation of ethnomathematics in multicultural education in primary schools in Banyumas, focusing on the use of Ngapak’s non-standard units in multiplication operations and the utilization of traditional games such as engklek and dam-daman in teaching geometry. Using a qualitative approach with a descriptive type, this study involved teachers, students, and school principals from three primary schools in Banyumas. Data were collected through semi-structured interviews, participatory observations, and document analysis, which were then interactively analyzed through data reduction, data presentation, and conclusion drawing. The study results show that: 1) the use of non-standard units such as unting, sangga, and selingget in multiplication operations enriches students' conceptual understanding by linking mathematics to real-life practices such as trade and agriculture, 2) the engklek game strengthens geometry concepts through representations of squares, rectangles, and triangles, while the dam-daman game contributes to the development of critical thinking, problem-solving skills, and spatial strategies, 3) this study proves that the ethnomathematics approach not only increases student engagement in learning but also contributes to academic achievement, with mastery levels ranging from 92% to 95% and average scores between 87 and 89.